Trade finance and exports: Firm-level evidence from China - Jiancong Liu; Marc Auboin; Beliyou Haile; Yu Wang (World Trade Organization (WTO), 2024)
We use panel data for listed firms from China for 2013-2021 to examine the association between their export earnings and trade finance, particularly those receiving trade loans. Results show that a percent increase in trade finance loan is associated with 0.067-0.083 percent increase in export earnings depending on the model. When we proxy trade finance by the sum of trade finance loans and export-adjusted notes receivable, elasticity estimates range between 0.18-0.31 depending on the sample of exporters. These estimates are comparable to single and multi-instrument trade finance instrument elasticities in the literature. Elasticity of export earnings is higher for smaller firms that may have relatively limited financing options from domestic capital markets. Given that listed firms represent the largest companies, we acknowledge that study findings may not be generalizable to the universe of highly heterogeneous Chinese traders. Nonetheless, our results suggest that well-functioning markets for trade finance are likely to enhance trade, while, by contrast, lack of affordable trade finance can be a barrier to trade, or a trade cost, in its own right.
Keywords: F10; G21; O16; F14; F19; 330; Trade; empirical studies on trade; trade finance